2019
DOI: 10.1039/c8cp05946b
|View full text |Cite
|
Sign up to set email alerts
|

The role of pH, metal ions and their hydroxides in charge reversal of protein-coated nanoparticles

Abstract: In this study, we investigated charge inversion of protein-coated Au nanoparticles caused by the addition of metal ions. Adsorbed metal hydroxides were identified to cause the charge inversion of the NPs by using a combination of cryo-TEM, EFTEM and ζ-potential measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…This shell connects the NPs and is also found in their immediate surroundings. As investigated by Schubert et al, 43 this shell can be attributed to the presence of Gd hydroxides and can be considered to be an argument for the aggregation of the nanoparticles via interactions of sulfonate groups with the Gd 3+ ions without replacement of the ligands from the rst coordination sphere of Gd. Together, reversibility of the interactions observed in QCM-D experiments and the possibility to reverse the particle aggregation by the addition of a strong coordinating ligand for the Gd 3+ ions, i.e.…”
Section: Origin Of Aggregation Of Aunp@bspp By Gd 3+mentioning
confidence: 88%
“…This shell connects the NPs and is also found in their immediate surroundings. As investigated by Schubert et al, 43 this shell can be attributed to the presence of Gd hydroxides and can be considered to be an argument for the aggregation of the nanoparticles via interactions of sulfonate groups with the Gd 3+ ions without replacement of the ligands from the rst coordination sphere of Gd. Together, reversibility of the interactions observed in QCM-D experiments and the possibility to reverse the particle aggregation by the addition of a strong coordinating ligand for the Gd 3+ ions, i.e.…”
Section: Origin Of Aggregation Of Aunp@bspp By Gd 3+mentioning
confidence: 88%
“…One of the first challenges in the synthesis of NPs is to achieve good colloidal stability and uniformly dispersed samples. 51 Therefore, the stability of NPs was evaluated as a function of time. Size and surface charge variations usually engender NP instability, with aggregation and precipitation over time.…”
Section: Stability Of Nanoparticlesmentioning
confidence: 99%
“…In addition to purely charge-mediated effects, cation-induced pH changes need to be considered as well. Schubert et al [455] studied the influence of metal ions and their hydroxides and the associated pH changes on NPs coated with BSA. This study reports both charge inversion of the NPs and a decrease of the solution pH upon addition of several trivalent cations, going along with the adsorption of metal hydroxide species on the NPs.…”
Section: Colloids and Nanoparticlesmentioning
confidence: 99%
“…This study reports both charge inversion of the NPs and a decrease of the solution pH upon addition of several trivalent cations, going along with the adsorption of metal hydroxide species on the NPs. Schubert et al [455] trace the charge inversion observed to these hydroxides, thus connecting pH and pure charge effects.…”
Section: Colloids and Nanoparticlesmentioning
confidence: 99%